(untitled) (GYMNASIUM, 2017)
The aim of our paper is to identify the level of student satisfaction in relation with their university experience. The satisfaction questionnaire was applied from June 1st to June 15th, 2013 to 126 master students following two masters programs: Fitness and Human Body Aesthetics (FHBA) and Leisure Sports and Extreme Sports (LSES). The respondents answered to a standardized questionnaire structured on interdependent levels. The subjects were asked to assess the level of satisfaction using a Likert scale from 1 to 5. The level of general satisfaction of the students from 2nd year is higher comparative with students from 1st year. In case of the same specialization group, the satisfaction was similar in both years. The results obtained allow us to continue our research in master programs in order to see if the content of study disciplines gave the students satisfactions for their work.